Synergism of zinc oxide nano-powder with active compound from turmeric and lemongrass as bacterial inhibitor - Lau, Gee Een; Che Abdullah, Che Azurahanim; Mohd Ghazali, Mohd Sabri; Che Ibrahim, Muhamad Syazlie (Institute of Research and Development, Walailak University, 2021)
Green nanoparticles are receiving great attention due to their broad fields of application. Plant extracts are promising sources, since the synergizing process is easy and cost-effective. Green synergism offers safer nanomaterials for both human health and the environment. The antimicrobial application of prepared nanoparticles is due to special capabilities at the nanoscale size. Green zinc oxide nanoparticles (ZnONPs) from lemongrass and turmeric revealed good antibacterial properties. Antibacterial active compounds were extracted from lemongrass and turmeric using methanol as a solvent. The extracts were introduced to zinc oxide solution to create synergized green ZnONPs and tested for their antibacterial properties. The samples were characterized by means of XRD, SEM, FTIR, and GC-MS. The zones of inhibition of synergized green ZnONPs were successfully measured using the disc diffusion method. The findings using gram-negative bacteria Escherichia coli. showed a higher antibacterial inhibition zone, with a diameter of 1.6 cm. The gram-positive bacteria, Staphylococcus aureus., showed low antibacterial inhibition. The addition of ZnO had positively revealed greater inhibition. Green ZnONPs synthesized using plant extracts will be further tested for various applications.